Estudos biossintéticos de amidas bis-fenilpropanoídicas produzidas pelo fungo Penicillium brasilianum, um endofítico de Melia azedarach (Meliaceae) - Fill, Taícia Pacheco (2009)
In the present work it was developed analytical methodologies for investigation of biosynthesis of bis-phenylpropanoyl amides, using labeled precursors in the culture medium. The effect of different nitrogen sources on the bis-phenylpropanoyl amides production was also evaluated. These amides are reported as antiparasitary compounds and they also showed activity against gram-positive Bacillus subtilis in bioassays conducted at LaBioMMi (DQ/UFSCar). The analytical methodologies developed were based on High Performance Liquid Chromatography (HPLC) and Mass Spectrometry techniques, mainly electrospray ionization (ESI) and MS/MS. Using the methodologies developed for preparative liquid chromatography it were isolated the bis-phenylpropanoyl amides, brasiliamide A and B and other secondary metabolites co-produced. Liquid chromatography coupled with mass spectrometry techniques allowed fragmentation studies which lead to selective detection experiments of brasiliamides in mediums enhanced with different nitrogen sources. The quantitative analysis (HPLC/UV-MS/MS) indicated great influence of the amino acid L-phenylalanine on the bis-phenylpropanoyl amides production. From these results, the biosynthesis of the phenylapropanoids was investigated using [2-13CPhe]. The RMN 13C and HPLC/UV-MS analysis showed the incorporation of two amino acid units on brasiliamides structure formed by the phenylpropanoids pathway, which is uncommon in fungi. The first phenylpropanoid pathway step was evaluated throw using enzymatic extract with Phenylalanine ammoniolyase (PAL). The HPLC/UV analysis indicates the formation of cinnamic acid from Lphenylalanine.